Intellectual, educational, and situation-based social outcome in adult survivors of childhood medulloblastoma. (2nd January 2019) - Kieffer, Virginie; Chevignard, Mathilde P.; Dellatolas, Georges; Puget, Stephanie; Dhermain, Frederic; Grill, Jacques; Valteau-Couanet, Dominique; Dufour, Christelle
ABSTRACT: Purpose : To investigate intellectual and situation-based social outcome and educational achievement in adult survivors of childhood medulloblastoma and analyse factors influencing outcome Methods : We collected demographic, medical and cognitive data, and social and educational outcome at a mean time since the end of treatments of 14.9 years in 58 adults, aged 19–35 years, consecutively treated in a single cancer center between 1989 and 2005. Results : Ten survivors had severe intellectual disability, 12 were still studying, 23 had a regular employment and 13 were unemployed. Full Scale Intellectual Quotient, assessed 6.6 years after the end of treatments, ranged from 46 to 131. It was strongly associated with educational achievement and significantly lower in patients who experienced postoperative cerebellar mutism, and when parental education level was low. Conclusion : These factors should be systematically considered at diagnosis in order to offer adequate and timely assessments and interventions.